2011
DOI: 10.1002/chem.201002451
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic and Reductive Electrochemical Switching of a Dithiazolylethene with Large Redox Modulation

Abstract: A new dipyridylthiazolylethene (1a) and its dicationic analogue (2a), with two N-methylated pyridyl rings, have been synthesized and structurally characterized. Due to the N-methylation of the pyridyl rings, 2 a displays not only very different photochromic properties, but also undergoes a reductive ring-closing reaction to generate its closed-ring isomer 2b. Careful electrochemical studies coupled with EPR spectroscopy show that this reductive ring-closing reaction takes place when 2a is two-electron reduced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 58 publications
3
27
1
Order By: Relevance
“…Except for rare examples of methylpyridinium substituted DTEs [ 27 28 ] and dithiazolylethenes [ 29 ], ring closure under reductive conditions has not been reported for DAEs. For most structures the reduction potential of the open isomer is too negative to be reached within the redox window determined by the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for rare examples of methylpyridinium substituted DTEs [ 27 28 ] and dithiazolylethenes [ 29 ], ring closure under reductive conditions has not been reported for DAEs. For most structures the reduction potential of the open isomer is too negative to be reached within the redox window determined by the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Either cyclization [ 5 13 ] or cycloreversion [ 14 21 ] can be observed, while correlation of both reaction modes to the molecular structure is still under discussion [ 22 26 ]. There are only few reports about reductive isomerization, each involving the ionic methylpyridinium group as a substituent on the photochromic unit [ 27 29 ]. However, by a combination of suitable substituents, a bidirectional system able to operate in both switching directions either electrochemically or photochemically has been reported [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] In comparison, examples of reductive electrocyclization are rare and generally require the presence of strong electron withdrawing groups such as N-methylpyridinium connected to the photochromic dithienylethene or dithiazolylethene core. [12][13][14] However, recent works showed that dithienylethenes with appropriate cyano-substitution or an extended π system could also lead to reductive ring-closure, albeit with much more negative potentials. [11] It is worth noting that in most cases the redox input triggers only one-way isomerization and cannot be used to bring the diarylethene back to its initial state.…”
Section: Introductionmentioning
confidence: 99%
“…[23] With regard to redox-responsive behavior, different terarylenes (aryl = thiazolyl, thienyl group or a combination of the two) have been reported to undergo oxidation induced ring-opening of their respective closed forms and, moreover, this ring-opening reaction was found to proceed via an auto-catalytic chain reaction mechanism with an efficiency well above 100 %, [24,25] but no reductive cyclization is known for terarylenes, to our knowledge. To investigate the possibility of combining both the oxidative ringopening and the reductive ring-closing reaction within terar-ylenes, we set up to design appropriately N-methylpyridiniumsubstituted terarylenes, since this functionalization is the most effective for triggering reductive cyclization of diarylethenes at accessible potentials, [12,14] and also to study how the properties of such a bi-directional photo-and redox-switch, if confirmed, could possibly be modulated by tuning the structure of the central aryl group. To this end, two dicationic terthiazole-based molecules are synthesized and fully characterized (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…But, most of them are nonfluorescent or show rather small photochromic fluorescence changes that restrain their applications in fluorescent modulation switches. To solve the problem, novel diarylethene systems with other heteroaryl moieties have been designed and synthesized, such as pyrrole , indole , furan , pyridine , and thiazole . Among them, thiazole is an attractive aryl unit because of its low aromatic stabilization energy and its structure is similar to those of thiophene.…”
Section: Introductionmentioning
confidence: 99%